Ulu Arif Çelebi Dönemi Mevleviliğin Gelişmesinde İlhanlilarin Etkisi - Akkuş, Mustafa (Journal of Alevism-Bektashism Studies, 2013)
Mevlana who is the most important litterateur, sufi and scholar lived in XIII century, continues his popularity with his ideas and life of thought with the same freshness in this age as well as he marked the century which he lived. Surely, the largest share belongs to his sons Sultan Veled and Ulu Arif Chalabi. In this article, after we have mentioned the Mawlavi in Sultan Veled period that became religious sect and their relations with Ilkhanids briefiy, we have explained the Mawlavi in Ulu Arif Chalabi period and Ilkhanid relations. We have tried to indicate the benefits of both sides, and we have emphasized Ilkhanids ınfiuence on spread of the Mawlavi.
Keywords: Mawlaviyya; Ulu Arif Chalabi; Ilkhanids; Mongols